Does public pension crowd out the participation of older adults in community volunteering? Evidence from China - Zhi-Yun Li; Ying-Yi Tang; Hua-Lei Yang; Li-Li Tang (Frontiers in Public Health)
BackgroundTo address aging and its associated social risks, the World Health Organization proposed an “active aging” policy framework in 2002, highlighting “health, participation, and security” as the three pillars for enhancing quality of life in old age. Extensive research has shown that public pensions, as a state-implemented social security measure, can effectively improve the health and well-being of older adults. However, existing studies have not sufficiently examined the causal impact of public pensions on social participation among older adults, such as community volunteering.MethodsUsing data from the China Longitudinal Aging Social Survey in 2018, this article employs propensity score matching (PSM) and control function (CF) approaches to empirically examine the impact of the Urban and Rural Resident Social Pension (URRSP) on the participation of older adults in community volunteering. Specifically, we investigate whether this relationship varies across social groups.ResultsEmpirical results indicate that, compared to uninsured older adults, those enrolled in the pension program show a significantly lower likelihood and frequency of volunteering. This finding is robust after controlling for observable and unobservable characteristics, thus supporting the crowding-out hypothesis. Furthermore, heterogeneity analysis reveals that this crowding-out effect is more pronounced among older adults with higher socioeconomic status, such as those living in urban areas, with higher education, higher income, and better health. In other words, the limited benefits provided by the URRSP not only fail to offer financial support for volunteering, but also significantly reduce the willingness and level of volunteering among those with higher socioeconomic status.ConclusionThe above findings confirm the crowding-out hypothesis, suggesting that in developing countries with underdeveloped and stratified social security systems, state-led public pensions may crowd out older adults’ participation in volunteer activities that are altruism and mutual support.